(untitled) (World Bulletin of Public Health, 2022)
Periodontitis and Atherosclerotic diseases are highly widespread diseases characterized by chronic inflammatory process. Through the last years, there has been an increase attention on the effect of oral health on atherosclerosis and other cardiovascular disease